O Partido como agente educativo em Gramsci - Freitas, Luiz Carlos de (2009)
In this work we seek to present Gramsci s conceptions of education and party, as well as to revise his theory of revolution. The role of the political party as an educational agent that idealizes and implements an education towards the rupture and overcoming of the capitalist society was also highlighted in this study. We assume that the party, according to Gramsci, goes beyond the institutionality and sometimes it is almost confused with the class itself. The same is true with education: to Gramsci, this is a human phenomenon that goes beyond formality, covering the whole culture built by a society. Central Gramscian concepts such as hegemony, civil society, war of position and war of movement are also addressed, since they are closely linked each other. These concepts are revised with a focus on the party as an educational agent, in an attempt of understanding the educational action of the party in the construction of hegemony, in the activity of civil society, and in the tactics to be used in each historical moment. Finally, we present the discussion on the organic and the traditional intellectual, as well as the educational relationship between the intellectuals and the party, and we also offer some reflections on the revolutionary praxis. According to Gramsci, every class, in all societies, form their organic intellectuals, who are responsible for maintaining the ideology that allows the operation of the economic, political and social model of their time. The traditional intellectuals are disputed by the ruling class and the working class; in this perspective, then, it is the function of the party not only to develop its organic intellectuals but also to conquer these other intellectuals to defend its ideology. The formal school, from which come the traditional intellectuals, is also the scene of a struggle between classes with antagonist projects of society. Thus, the role of the political party, in the Gramscian conception, is to act as an educational agent in the various segments of the civil society, disputing the hegemony for the construction of a revolutionary education focused on the working class.